Vascularized Bone Grafts for Spinal Fusion—Part 4: The Scapula. Issue 5 (22nd February 2021) - Reece, Edward M; Davis, Matthew J; Abu-Ghname, Amjed; Chamata, Edward; Holmes, Scott; Winocour, Sebastian; Hansen, Scott L; Xu, David S; Bohl, Michael A; Ropper, Alexander E
Abstract: BACKGROUND: Solid arthrodesis is the long-term goal of most spinal reconstruction surgeries. A multitube of biologics as well as autograft is commonly used to augment the bony fusion. Medial scapular vascularized bone grafts (S-VBGs) are a novel approach to supplement cervicothoracic arthrodesis in patients at high risk for failed fusion. OBJECTIVE: To discuss the benefits of using a vascularized scapular graft, pedicled to the rhomboid minor, compared to both nonvascularized bone grafts and free vascularized bone grafts, as well as the surgical technique, feasibility, and nuances of the surgical experience with an S-VBG. METHODS: The anatomic feasibility of this procedure has been established in cadaver studies. This technical note details the operative steps and presents the first surgery in which a vascularized scapular graft was used to supplement cervicothoracic arthrodesis. RESULTS: A single patient with complex cervical deformity was successfully treated with this novel arthrodesis approach. CONCLUSION: Vascularized scapula grafts, pedicled on the rhomboid minor, provides both structural support and a source of vascularized autograft to a cervicothoracic arthrodesis. It leverages the benefits of a free-flap bone with less operative time and morbidity.